Optymalizacja systemu transportu jako warunek zrównoważonego rozwoju UE - Korletjanu, Jerzy (Optimisation of the Transport System as a Determinant of the Process of Sustainable Growth within the European Union, 2005)
The paper presents guidelines of the optimisation the European transport system, which are the determinants of the process of sustainable growth within the European Union. The process of transport system optimisation is provided by the instruments of European transport policy. The results of implementation the European transport policy are the liberalisation of the common transport market and the process of the European transport infrastructure harmonisation. Optimal European transport system is the stable system from economical, social and ecological point of view.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1071, t. 2, s. 128-133